Anesthetic management for percutaneous minimally invasive fetoscopic surgery of spina bifida aperta: a retrospective, descriptive report of clinical experience - Arens, Christoph; Koch, Christian; Veit, Mirko; Greenberg, Robert Steven; Lichtenstern, Christoph; Weigand, Markus A.; Khaleeva, Anastasiia; Schürg, Rainer; Kohl, Thomas (Anesthesia & analgesia, 2017)
Minimally invasive fetoscopic surgery for spina bifida aperta is a new therapeutic approach to preserve neurologic function by protecting exposed neural tissue. The anesthetic management is of paramount importance for the success of the procedure. Therefore, our protocol was developed with particular attention to safe and adequate maternal and fetal anesthesia, sufficient uterine relaxation as well as prevention of pulmonary edema, placental abruption, and spontaneous labor. As illustrated by this retrospective analysis of 61 cases, these goals can be reliably achieved. The clinical protocol is presented as a supplemental digital content to this manuscript (Supplemental Digital Content 1, http://links.lww.com/AA/B733).